Through the Viewfinder: Reflecting on the Collection and Analysis of Classroom Video Data - Fitzgerald, Angela; Hackling, Mark; Dawson, Vaille (University of Alberta * International Institute for Qualitative Methodology, 2013)
The possibilities inherent in the collection and use of video footage point to an important innovation for classroom research. Unfortunately, researchers often experience uncertainty about incorporating video into their methodological approach as it can present a potential minefield of operational, technical, and ethical issues that require consideration and negotiation. Nevertheless, with the increased emphasis on the use of digital technologies, the timing is right to engage in more in-depth discussions about the role of video data in education research. In contributing to this discussion, this article unpacks several issues connected to the use of video technology as a tool for data collection and analysis. This article focuses on addressing some of the barriers faced by education researchers such as making sampling decisions, maintaining research authenticity, and grappling with ethical issues that arise. In terms of the advantages for researchers, this article highlights the suitability of video technology for classroom-based research because it provides a permanent and detailed record, which can be analyzed from multiple perspectives. These issues are explained through the experiences of an education researcher, who used video as the main data source for documenting and examining the practices of two effective primary science teachers in Perth, Western Australia.